Conduite De Changement Organisationnel Dans Le Secteur De Santé Marocain. Cas Du Centre Hospitalier Regional D’agadir - Rachid Zammar; Noureddine Abdelbaki (European Scientific Journal, ESJ, 2016)
This article proposes a clarification of driving organizational change in the Moroccan health sector and levers used to set up and considers the following question: how the establishment of hospital project (EHP) proves as tool driving change in the Moroccan health sector? The methodology is based on an exploratory study among the staff of a particular hospital which is the regional hospital of Agadir (CHRA). The main conclusion of the study is that the implementation of the EHP, at the CHRA enabled the upgrade of the hospital. However, alone man cannot make the change, the financial and technical resources have a clear role in improving care services to the population.